2015
DOI: 10.1002/2014jb011713
|View full text |Cite
|
Sign up to set email alerts
|

Reexamination of magnetotelluric responses and electrical anisotropy of the lithospheric mantle in the Grenville Province, Canada

Abstract: Magnetotelluric (MT) responses at the Proterozoic Grenville Front in Canada have been interpreted as being caused by lithospheric electrical anisotropy, and the area is often noted as a classic example of lithospheric anisotropy. This study reevaluates evidence for the electrical anisotropy using 56 MT stations. The spatially uniform MT responses noted at the Grenville Front extend to~200 km southeast and for at least 400 km along strike and are associated with rocks at less than 150 km depth. Examination of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 79 publications
0
12
0
Order By: Relevance
“…A major difficulty in these measurements is that azimuthal variation in the MT response may also result from larger-scale variations in electrical conductivity (heterogeneity). For instance, recent re-examination of MT data in the Grenville concluded that the observed signal records extension of the resistive Archean lithosphere beneath the Greenville front rather than conductivity anisotropy in the lithospheric mantle, which is constrained to be <10% (Adetunji et al, 2015).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…A major difficulty in these measurements is that azimuthal variation in the MT response may also result from larger-scale variations in electrical conductivity (heterogeneity). For instance, recent re-examination of MT data in the Grenville concluded that the observed signal records extension of the resistive Archean lithosphere beneath the Greenville front rather than conductivity anisotropy in the lithospheric mantle, which is constrained to be <10% (Adetunji et al, 2015).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Electrical conductivity of Cpx‐NaCl‐H 2 O systems with various salinities calculated based on HS + and Cube models and high‐conductivity layers in southern Tibetan Plateau (Xie et al, 2016), Dabie Orogen (Xu et al, 2016), Grenville province (Adetunji et al, 2015), and central New Zealand (Wannamaker et al, 2009). Colored solid and dashed lines represent the electrical conductivities of Cpx‐NaCl‐H 2 O systems calculated based on the HS + and Cube models, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…It should also be noted that a given resistivity structure may not necessarily produce its MT and IV responses at the same period range (Wannamaker et al 1984). Adetunji et al (2014Adetunji et al ( , 2015 showed that both the MT and induction vector responses could be modelled successfully with macroscopic 2-D resistivity structures. Further, Weckmann (2006) showed that phase splits from off-profile 3-D conductors could be misinterpreted as evidence for electrically anisotropic resistivity structure.…”
Section: -D or 2-d Anisotropic?mentioning
confidence: 99%